Bottled water- problem in campus - Chandwani, Rajesh; Varkkey, Biju; Kadamberi, Vidya (London : Indian Institute of Management, Ahmedabad, 2019)
The case is based on heated email conversations regarding the delivery of clean bottled water in the campus of a reputed research Institute, Arumalai Research Institute, in Southern India. The conversations were between Tara Sharma (Programme Manager - Executive Programme Division) and Shreejith Nair (Head-Engineering, Service & Estate). The case presents the viewpoints of various stakeholders involved in the open conversation.
Originally Published InChandwani, R., Varkkey, B., & Kadamberi, V. (2019). Bottled Water- Problem in Campus. IIMA/HRM0240. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Bottled water -- India -- Case studies; Universities and colleges -- India -- Water-supply -- Case studies